Integrasi Nilai-Nilai Hak Anak Dalam Pai: Membangun Karakter Generasi Berbasis Al-Qur'an Dan Hadist - Apriyani, Hikma; Ajir, Ikhtiar Cahya; Erlina, Erlina; Hijriyah, Umi (Institut Agama Islam Ngawi, 2024)
Islamic Religious Education (IRE) in elementary schools plays a crucial role in shaping the character of the younger generation based on the Qur'an and Hadith. However, there are still challenges in integrating children's rights values into the Islamic Education curriculum. This research discusses the importance of incorporating children's rights values in Islamic Education to build the character of a morally upright generation. The background is the need to raise awareness of children's rights in religious education. The purpose of this research is to understand how the PAI curriculum can integrate children's rights values and how this implementation can shape better student character. The research method involves analyzing the existing PAI curriculum, interviewing teachers and students, and observing teaching and learning activities. The results of this research indicate that incorporating children's rights values can enhance students' understanding of their rights and foster a more ethical character. Therefore, effective implementation strategies require an integrated curriculum, active learning methods, extracurricular activities, and the participation of parents and the community.